Foundations of Digital Government Leading and Managing in the Digital Era - Veit, Daniel; Huntgeburth, Jan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Digital government consists in the purposeful use of information and communication technologies (ICT), in particular the internet, to transform the relationship between government and society in a positive manner. This book focuses on the current status, prospects and foundations of digital government. Integrating examples and cases from administrative practice, it covers all important aspects of digital government management. Learning outcomes include Understanding the implications of the internet for government and society Gaining deeper insights into the concept and opportunities of digital democracy Understanding the challenges of moving public services online
Preface -- 1 Introduction to Digital Government -- 2 Impact of Digital Government -- 3 The Digital Divide -- 4 Legal Aspects of Digital Service Delivery -- 5 Online One-Stop Government -- 6 Open Government -- 7 E-Procurement -- 8 E-Voting -- 9 E-Participation -- 10 Lesson Learned and Outlook.
Keywords: Economics; Computer science; Computers -- Law and legislation; Information Systems; Management information systems; Economics/Management Science; Business Information Systems; Public Administration; Computers and Society; Management of Computing and Information Systems; Legal Aspects of Computing; Political Science, general